PRESIDENT INFANTINO: THE CHALLENGE OF RESTORING CREDIBILITY TO FIFA - Alamo, Pablo; Prada, Francisco; Gómez, Jaime Alonso (My University, 2025)
The case addresses the dilemma faced by FIFA President Gianni Infantino in the days leading up to the 2022 Qatar World Cup, amid intense public criticism and calls for a boycott. The decision to award the first World Cup in the Middle East was made in 2010 during the presidency of Joseph Blatter, when Infantino was Secretary General of UEFA. Since then, the choice of Qatar has raised suspicions of irregularities and bribery, severely undermining FIFA’s legitimacy. With growing international pressure just weeks before the tournament began, Infantino was forced to define a communication strategy in response to an institutional crisis that threatened not only FIFA’s reputation but also its credibility as a trustworthy leader. The case places students in Infantino’s position, challenging them to reflect on how to respond—whether with silence, defense, or critical distancing— while balancing the pressures from sponsors, governments, media, and civil society organizations.18
Keywords: Credibilidad; FIFA; Campus Tijuana